Advances in 2D Material Transfer Systems for van der Waals Heterostructure Assembly - Ratchanok Somphonsane; Kanokwan Buapan; Harihara Ramamoorthy (My University, 2024)
The assembly of van der Waals (vdW) heterostructures using 2D material transfer systems has revolutionized the field of materials science, enabling the development of novel electronic and optoelectronic devices and the probing of emergent phenomena. The innovative vertical stacking methods enabled by these 2D material transfer systems are central to constructing complex devices, which are often challenging to achieve with traditional bottom-up nanofabrication techniques. Over the past decade, vdW heterostructures have unlocked numerous applications leading to the development of advanced devices, such as transistors, photodetectors, solar cells, and sensors. However, achieving consistent performance remains challenging due to variations in transfer processes, contamination, and the handling of air-sensitive materials, among other factors. Several of these challenges can be addressed through careful design considerations of transfer systems and through innovative modifications. This mini-review critically examines the current state of transfer systems, focusing on their design, cost-effectiveness, and operational efficiency. Special emphasis is placed on low-cost systems and glovebox integration essential for handling air-sensitive materials. We highlight recent advancements in transfer systems, including the integration of cleanroom environments within gloveboxes and the advent of robotic automation. Finally, we discuss ongoing challenges and the necessity for further innovations to achieve reliable, cleaner, and scalable vdW technologies for future applications.
Keywords: Cleanroom; 2D Materials and Applications